Autologous haematopoiesis stem cell transplantation (AHSCT) for treatment-refractory autoimmune diseases in children - Jasmin Beate Kuemmerle-Deschner; Susanne Benseler; Joerg C Henes; Özlem Satirer; Michaela Döring; Till Lesk (RMD Open)
Objectives To evaluate the long-term effectiveness and safety of autologous haematopoiesis stem cell transplantation (AHSCT) for severe, refractory autoimmune diseases in paediatric patients.Methods A single-centre study of consecutive children and adolescents with refractory autoimmune diseases undergoing AHSCT was performed. Demographics, clinical, laboratory features, pre-AHSCT medications, disease activity and functional status were captured. The primary outcome was progression-free survival, secondary outcomes included overall survival, disease-specific treatment responses, disease activity at the last follow-up and AHSCT safety.Results The study included seven patients: two systemic sclerosis, one pansclerotic morphoea, one eosinophilic fasciitis, one juvenile dermatomyositis and two patients with systemic juvenile idiopathic arthritis; four women, three men median age at AHSCT of 10 years (7–19), median follow-up post-AHSCT of 17 years. Median progression-free survival and overall survival was 4.2 years (95% CI: 0.98 to 8.3) and 17 years (95% CI: 11.8 to 22.1), respectively. Progression-free survival rates at 1 and 2 years post-AHSCT were 100% and 77%, respectively. All children survived. All patients are in clinical remission, only four require ongoing immunotherapy. Safety: Three experienced infections, including HHV6, Candida and Ralstonia sepsis; one developed a systemic inflammatory response syndrome; two new onset secondary autoimmune diseases including autoimmune haemolytic anaemia, Graves’ disease and one was found to have a breast fibroadenoma. Treatment toxicity: one cyclophosphamide-associated transient renal failure and pericardial effusion, one patient with amenorrhoea/infertility.Conclusions AHSCT was an effective and safe approach for children and adolescents with treatment-refractory autoimmune diseases. The indication and timing of transplantation requires a careful consideration and a multidisciplinary approach.